Development of Musical Taste - Kopinšek, Katarina (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter focuses on the development of musical taste and the factors that shape an individual's musical preferences. Musical taste is dynamic, evolving throughout life, and is closely linked to personal identity, emotions, and lifestyle. Its development is influenced by upbringing, social circles, personal experiences, and exposure to various genres. The chapter also references research highlighting the role of educational institutions, where the school system often prioritizes classical music, potentially leading to bias. Musical preferences also vary across social classes, with the upper classes tending to favour classical music, while the lower classes often prefer folk music. Additionally, the teacher plays a significant role in actively shaping children's preferences through the selection of musical material. High-quality music and the teacher's methodological expertise are essential for developing pupils' ability to distinguish between high- and low-quality music.